Rethinking 'marketing as applied economics'. (December 2022) - Tadajewski, Mark
This paper makes three intertwined arguments. Firstly, marketing is not simply an outgrowth of economics. Secondly, it is indebted to metaphysical, psychical and psychological research which provided the conditions of possibility for theorising marketplace interaction in our early history. Thirdly, marketing thinking has been and remains inflected by a position labelled 'practical idealism'. It is a contrast to the 'practical realism' which also subtends our discipline. Adopting a genealogical approach, we explicate the threads of practical idealism weaved across Prentice Mulford, Thomson J. Hudson and A.F. Sheldon's prominent works. Mulford provides the contours of the intellectual landscape. Hudson extends Mulford's assumption grounds. Sheldon combines the articulations of Mulford, Hudson and studies in psychical research, outlining the viability of hypnosis and telepathy in sales practice. To distance itself from hypnosis and associations of manipulation, 'suggestion' was the epistemological-political replacement promoted by marketing theorists. Discursive transmutation was achieved through epistemological deviation . Epistemological deviation is conceptualised as the dismissal of and disengagement from a theoretical or hypothetical account without the consideration of appropriate evidence. W.D. Scott's treatment of telepathy is an exemplar of epistemological deviation. It is a complete departure from the tenets of intellectual inquiry. What this means is that the promotion of psychology into marketing was accomplished – in part – by the abdication of critical reflection and not by its extension.